A comparison of the responses of mature and young clonal tea to drought. - Nixon, D. J.; Burgess, Paul J.; Sanga, B. N. K.; Carr, M. K. V. (Cambridge University Press, 2001)
To assist commercial producers with optimising the use of irrigation water, the responses to drought of mature and young tea crops (22 and 5 years after field planting respectively) were compared using data from two adjacent long-term irrigation experiments in Southern Tanzania. Providing the maximum potential soil water deficit was below about 400-500 mm for mature, and 200-250 mm for young plants (clone 6/8), annual yields of dry tea from rainfed or partially irrigated crops were similar to those from the corresponding well-watered crops. At deficits greater than this, annual yields declined rapidly in young tea (up to 22 kg (ha mm)-1) but relatively slowly in mature tea (up to 6.5 kg (ha mm)- 1). This apparent insensitivity of the mature crop to drought was due principally to compensation that occurred during the rains for yield lost in the dry season. Differences in dry matter distribution and shoot to root ratios contributed to these contrasting responses. Thus, the total above ground dry mass of well-irrigated, mature plants was about twice that for young plants. Similarly, the total mass of structural roots (>1 mm diameter), to 3 m depth, was four times greater in the mature crop than in the young crop and, for fine roots (<1 mm diameter), eight times greater. The corresponding shoot to root ratios (dry mass) were about 1:1 and 2:1 respectively. In addition, each unit area of leaf in the canopy of a mature plant had six times more fine roots (by weight) available to extract and supply water than did a young plant. Despite the logistical benefits resulting from more even crop distribution during the year when crops are fully irrigated, producers currently prefer to save water and energy costs by allowing a substantial soil water deficit to develop prior to the start of the rains, up to 250 mm in mature tea, knowing that yield compensation will occur later.